Severe Neurotoxicity due to Atropa belladonna Poisoning: A Case Report and Literature Review - Seyed Javad Boskabadi; Sima Ramezaninejad; Zakaria Zakariaei (Case Reports in Neurological Medicine)
Atropa belladonna (A. belladonna), commonly known as deadly nightshade, is a poisonous plant belonging to the Solanaceae family. The toxic effects of A. belladonna are attributable to its alkaloid content, which possesses potent anticholinergic properties. These alkaloids are responsible for the plant’s toxicity and can cause a range of adverse effects in humans and animals upon ingestion or contact. In this report, we describe two atypical cases of A. belladonna poisoning resulting from accidental ingestion of the plant’s raw leaves, which were referred to the emergency room of a poisoning center in northern Iran. Both patients presented with symptoms of anticholinergic toxicity, including dry mouth, mydriasis, tachycardia, and delirium. The patients were managed conservatively with supportive measures, including hydration and administration of benzodiazepines to control agitation and delirium. With appropriate treatment, both patients showed improvement and were discharged from the hospital. A. belladonna intoxication is associated with a range of clinical manifestations, primarily due to its neurotoxic effects. These manifestations may include flushing, mydriasis, tachycardia, ataxia, agitation, delirium, and urinary retention. The severity of symptoms can vary depending on the amount of the toxin ingested and the individual’s susceptibility. In severe cases, A. belladonna toxicity can lead to seizures, coma, and even death. These cases highlight the importance of awareness regarding the potential toxicity of A. belladonna and the necessity of prompt and appropriate management of its toxicity. In severe cases, physostigmine may be considered for the treatment of neurological symptoms due to the plant’s anticholinergic effects.